Features of diagnostics and surgical treatment of acute anaerobic paraproctitis - E. E. Bolkvadze (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To develop medical approach at acute anaerobic paraproctitis (AAP).Materials and methods. In 1997–2006 in urgent proctology department The SSC of coloproctology 4046 patients with various types of acute paraproctitis were operated. Original study included 140 patients, 20 to 86 years old (mean age made 57,1±3,9 years) with anaerobic paraproctitis. Investigation included general physical examination, digital examination of the rectum and rectoromanoscopy, transabdominal and transrectal ultrasound, bacteriological study of wound exudate and morphological study of affected pararectal fat. Ultrasound investigation was supplemented by computer tomography for differential diagnostics. Surgical interventions in all cases was carried out under urgent indications. Severity of patients state and efficacy of treatment was evaluated by SAPS and SOFА scoring systems.Results. Three clinical forms of AAP were defined: fulminant, acute and subacute. In relation to etiological agent type following forms of anaerobic paraproctitis were determined: clostridial, non-clostridial and purulent. Forty-five percent of patients admitted in severe and extremely severe state, 25,7% addressed for medical care 7 days and later after onset of disease. Mortality was 15,7% – all of the were patients, that admitted in extremely severe state. Extrasphincter fistulas were formed in 11 (10,8%) patients.Conclusion. The success of treatment of patients with AАП in many respects depends on early diagnostics of inflammatory process, early urgent surgery with essential and extensive enough necretomy and adequate intensive care.